Effect of Fecal Microbiota Transplantation Combined With Mediterranean Diet on Insulin Sensitivity in Subjects With Metabolic Syndrome - Koopen, Annefleur M.; Almeida, Eduardo L.; Attaye, Ilias; Witjes, Julia J.; Rampanelli, Elena; Majait, Soumia; Kemper, Marleen; Levels, Johannes H. M.; Schimmel, Alinda W. M.; Herrema, Hilde; Scheithauer, Torsten P. M.; Frei, Werner; et al. (Frontiers in Microbiology, 2021)
Background: Recent studies demonstrate that a Mediterranean diet has beneficial metabolic effects in metabolic syndrome subjects. Since we have shown that fecal microbiota transplantation (FMT) from lean donors exerts beneficial effects on insulin-sensitivity, in the present trial we investigated the potential synergistic effects on insulin-sensitivity of combining Mediterranean diet with donor FMT in subjects with metabolic syndrome. Design: Twenty-four male subjects with metabolic syndrome were put on a Mediterranean diet and after a two-week run-in phase, subjects were randomized to either lean donor (n=12) or autologous (n=12) FMT. Changes in gut microbiota composition and bacterial strain engraftment after 2-week dietary regimens and 6 weeks post-FMT were primary endpoints. Secondary objectives were changes in glucose fluxes (both hepatic and peripheral insulin sensitivity), postprandial plasma incretin (GLP-1) levels, subcutaneous adipose tissue inflammation and plasma metabolites. Results: Consumption of the Mediterranean diet resulted in a reduction in body weight, HOMA-IR and lipid levels. However, no large synergistic effects of combining the diet with lean donor FMT were seen on gut microbiota diversity after 6 weeks. Although we did observe changes in specific bacterial species and plasma metabolites, no significant beneficial effects on glucose fluxes, postprandial incretins or subcutaneous adipose tissue inflammation were detected. Conclusions: In this small pilot randomized controlled trial, no synergistic beneficial metabolic effects of combining Mediterranean diet with lean donor FMT on glucose metabolism were achieved. However, we observed engraftment of specific bacterial species. Future trials are warranted to test the combination of other microbial interventions and diets in metabolic syndrome.